The Ways of Character Development in Some Contemporary Syrian novels - العلي باسمة; مغربي فاروق (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The character in the novel represents an effective factor in the process of novelistic structure, for at this very point all of the novel’s factors coincide and consequently lead to the completion of novelistic structure. All of the authors sough different techniques to present the character to the receiver. And drew the character in their novels in details. This research is presented as one reading of character presentation via the self-presentation as to unravel its existence, and via the indirect presentation. Thus, Self-presentation of the characters has defined their features, inscribed their psychological suffering, and unravel the extent to which each character has absorbed itself. Moreover, indirect presentation of the characters has presented them as social and psychological states enchained within a big frame of transformations.